The Relationship Between Anatomy Identification Test Scores and The Suitability in V/A/R/K Modality Usage Between Study Habit and Learning Style - Widiartini, Catharina; Ferine, Miko; Pribadi, Fajar Wahyu (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2024)
Background: Mastery of Anatomy is essential to base learning in Medicine. However, the Anatomy identification test scores are often less than satisfactory. This problem could be caused by different usage of sensory modalities which were visual, aural, read/write, and kinaesthetic (V/A/R/K) between one’s study habit and his/her learning style. This study aimed to determine the relationship between Anatomy identification test scores and the suitability in V/A/R/K modality usage between study habits and learning styles.Method: This was an observational study of 103 first year students of the Faculty of Medicine Unsoed who were selected using total sampling, taking into account the inclusion criteria in the form of complete data availability for the three variables. Univariate statistical analyses were conducted for each variable as well as the suitability between study habits and learning style based on determined criteria. Relationship between Anatomy identification test scores and the suitability between V/A/R/K study habits and learning styles was analyzed using the Mann-Whitney test.Results: Most students had quadmodal learning style (27.2%), but unimodal visual study habit (21.4%). Most (64.1%) students had no suitability between study habits and learning styles, with the test score average was not significantly lower (p = 0.228) than those with suitability. Conclusion: There is no significant relationship between Anatomy identification test scores and the suitability between study habits and learning styles. Students may reflect on the result to modify their learning process further. Institution can provide opportunities for students with various characteristics to develop study habits that suit their learning styles.